Training induced changes in the ground reaction force pattern of high knee sprinting in track and field jumpers - Rousanoglou, E.; Boudolos, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: A widespread coach belief is that high knee sprinting (HNS) improves the speed components by increasing the stride length and the body`s forward propulsion (Thompson et al., 2009; Young, 2012). To the best of our knowledge, there is lack of data regarding the HNS ground reaction force (GRF) pattern. The purpose of the study was a) to compare the HNS GRF pattern between track and field jumpers (TFJ) and untrained controls (CG) and b) to test the TFJ training induced changes. Methods: Twelve young women TFJ (14 to 19 yrs, elite level for their age category) performed HNS in place ( istler forceplate, 9286AA, 1000 z, 15s, as fast as possible). TFJ were tested during the beginning of the preparation period (Pre) (regular training thereafter) and 5 months later (Post). The CG (n = 12 age matched young women) was tested at same time period as the TFJ. Data included HNS frequency and, for the leading (LdL: limb of initiating knee lifts) and trailing (TrL) limb, respectively, contact time, flight time, peak vertical force, time to peak vertical force, total vertical impulse and reactivity index (flight to contact time ratio). Paired t-tests were used for the differences between TFJ and CG, as well as, between Pre and Post in each group (SPSS, 21.0, p 0.05). Results: No significant Pre to Post difference was found for CG. In the TFJ, all HNS variables remained unchanged between Pre and Post, except for the increased HNS frequency (Pre: 3.8 0.4 Hz, Post: 4.1 0.2 Hz). Compared to CG, the TFJ had significantly higher frequency only in Post (TFJ: 4.0 0.2 Hz, CG: 3.6 0.6 Hz). In both Pre and Post, TFJ had shorter contact times (p < 0.05), greater LdL reactivity index (p < 0.05) and, greater LdL impulse (p < 0.05). Discussion: HNS in place shows significant differences between TFJ and untrained CG already at the initiation of the preparation period with the TFJ training induced changes in reflecting a positive outcome for improved speed (Thompson et al., 2009). The advantageous impact of HNS lies in the increased pre-stretch of the gluteus and the hamstrings muscles of the swing leg when the hip joint comes to a position of greater flexion (Schache et al., 1999; Thompson et al., 2009). Together with the greater limb acceleration due to greater angular range of thigh motion, HNS allows an increased GRF during contact phase, which is positively related to increased speed (Schache et al., 1999; Thompson et al., 2009).